The role of polycomb group protein EZH2 in dendritic cell function. - Gunawan, Merry. (2012)
Positively charged lysine residue is subjected to a plethora of post-translational modifications. Lysine methylation, while mostly studied on histone, was shown to play an exquisite role in the regulation of many cellular processes. Alone, or in combination with other post-translational modifications, lysine methylation was shown to critically alter the function, interaction properties and stability of its substrates. Lysine methyltransferase Ezh2 was found in the nucleus where it exerts its epigenetic silencing function through histone methylation, and in the cytosol where it plays an unexpected role in cytoskeletal rearrangements.